Implementation Of Management Standards In Improving The Quality Of Academic Services In Elementary School - Noviyani , Selvi; Wasliman, Iim; Hanafiah, Hanafiah; Gaffar, Andriana (CV. Inara, 2022)
This research is motivated by the phenomenon of various problems faced by education units, such as lack of competence of principals, teacher linearity, shortage of teachers and education staff, minimal infrastructure and low academic services. Management of education that refers to standard management guidelines is one solution that can be taken in implementing the implementation of education management. The purpose of this study in general is to describe and analyze the implementation of management standards in improving quality academic services at SDN 1 Courts and SD Laboratorium UPI Tasikmalaya City. Specifically, to determine the indicators in the implementation of management standards, including: (1) planning, (2) organizing, (3) implementation, (4) evaluation, (5) problems, (6) solutions. The method used is a descriptive method with a qualitative approach. Data was collected through observation, interviews, and documentation studies. Data analysis was carried out by collecting all information, reducing data, presenting data and drawing conclusions. Theories that support the research are management theory, and integrated quality management theory. The results of the study indicate that in general both elementary schools have implemented education management standards quite effectively, educational units are increasingly competitive, the quality of graduates has improved with quality academic services. In particular, indicators in the implementation of education management are in accordance with applicable standards, including: (1) planning carried out by formulating vision and mission, setting goals and school curriculum; (2) organizing, namely the establishment of an organizational structure, making the division of tasks for educators and education staff, providing infrastructure; (3) program of activities according to procedures; (4) evaluation, namely by conducting program effectiveness, follow-up plans and stakeholder satisfaction levels; (5) problems, including human resources in providing academic services, infrastructure facilities for supporting the academic service process, budget for academic service activities (6) solutions include, human resource problem solutions, budgets and infrastructure. These indicators have been implemented by both elementary schools, but in general they lack a complete procedure, which is not based on the results of problem identification and optimization of academic services, but tends to be based on the judgment of academic service providers in elementary schools.